Pengaruh Kenyaman Pada Komunikasi Getok Tular Daring - Kristiantoro, Vinsent Ferry; Atmoko, Waluyo Budi; Sugiyarmasto, Sugiyarmasto (Jurnal Bisnis dan Kewirausahaan, 2021)
This study aims to examine the effect of online consumer satisfaction on online word-of-mouth, the effect of convenience of access on online consumer satisfaction, the effect of transaction convenience on online consumer satisfaction and the effect of service convenience on online consumer satisfaction. Online word of mouth or electronic word of mouth is currently a trend that is proven to be able to influence the buying behavior of a consumer.The data in this study were obtained through questionnaires distributed to the general public. The sample used is 200. The sampling technique used is purpose sampling. Testing the validity and reliability used SPSS. Hypothesis testing is done by using SEM (Structural Equation Modeling) analysis.The results in this study indicate that the four hypotheses are supported. The online consumer satisfaction variable has a positive effect on online word-of-mouth. Access convenience variable has a positive effect on online consumer satisfaction. The transaction convenience variable has a positive effect on online consumer satisfaction. And the service convenience variable has a positive effect on online consumer satisfaction. The results of this study mean that the convenience provided by an online application will give a sense of satisfaction to the individual and be able to have a positive impact on the individual doing word-of-mouth online.